Integrasi Nilai Dan Kearifan Lokal Papua Dalam Program Kampung Keluarga Berkualitas (KB) Studi Kasus di Kampung Skouw Yambe Distrik Muara Tami Kota Jayapura - Yohannes Rahail; Joseph Andhika Rahail; Renny Threesje Tumober; Irja Sepriyanto Jenmau (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
The Quality Family Village Program (Kampung KB) is a government strategy to improve family well-being by strengthening population development, family planning and family development. However, the implementation of this program in Papua still faces challenges regarding social acceptance due to the strong influence of cultural values, traditional social structures and community perceptions of family planning programs. This study aims to examine the local values and wisdom of the Papuan community that can be integrated into the implementation of the Kampung KB Program in Skouw Yambe Village, Muara Tami District, Jayapura City. The study employed a descriptive qualitative approach with informants selected through purposive sampling, including representatives of the “3-Tungku” (customary leaders, religious leaders and village government officials) and the “2-Peran” (women and youth). Data were collected through in-depth interviews and Focus Group Discussions (FGDs), then analyzed through data reduction, categorization and interpretation. The research findings indicate that integrating local values and wisdom can strengthen the implementation of the Kampung KB Program through three main mechanisms, namely: (1) a communication approach based on local philosophy through the traditions of eating betel nut and papeda as symbols of togetherness and social collaboration; (2) aligning the structure of the Kampung KB Working Groups (Pokja) with existing customary institutions to enhance legitimacy and a sense of community ownership; and (3) utilizing betel nut platforms and customary platforms as venues for socialization and participatory decision-making. These findings indicate that the integration of local wisdom can increase community participation, strengthen social acceptance and support the sustainable implementation of the Kampung KB Program in Papua through a development approach that is contextual and adaptive to the community’s sociocultural characteristics.